The reconsolidation using rewind study (RETURN): trial protocol - Laurence Astill Wright; Kali Barawi; Natalie Simon; Catrin Lewis; David Muss; Neil P. Roberts; Neil J Kitchiner; Jonathan I Bisson (European Journal of Psychotraumatology, 2021)
Background: An increasing body of research highlights reconsolidation-based therapies as emerging treatments for post-traumatic stress disorder (PTSD). The Rewind Technique is a non-pharmacological reconsolidation-based therapy with promising early results, which now requires evaluation through an RCT. Objectives: This is a preliminary efficacy RCT to determine if the Rewind Technique is likely to be a good candidate to test against usual care in a future pragmatic efficacy RCT. Methods: 40 participants will be randomised to receive either the Rewind Technique immediately, or after an 8 week wait. The primary outcome will be PTSD symptom severity as measured by the Clinician-Administered PTSD Scale for DSM5 (CAPS-5) at 8 and 16 weeks post-randomisation. Secondary outcome measures include the PTSD Checklist (PCL-5), International Trauma Questionnaire (ITQ), Patient Health Questionnaire (PHQ-9), the General Anxiety Disorder-7 (GAD-7), Insomnia Severity Index, the Euro-Qol-5D (EQ5D-5 L), the prominence of re-experiencing specific symptoms (CAPS-5) and an intervention acceptability questionnaire to measure tolerability of the intervention. Conclusions: This study will be the first RCT to assess the Rewind Technique. Using a cross-over methodology we hope to rigorously assess the efficacy and tolerability of Rewind using pragmatic inclusion criteria. Potential challenges include participant recruitment and retention. Trial registration: ISRCTN91345822